Patient with Down syndrome and relapsed acute lymphoblastic leukemia with sustained remission despite only partial R3 chemotherapy. Issue 3 (12th February 2021) - Hu, Zhongbo; VanHeyst, Kristen A.; Dalal, Jignesh; Hackney, Lisa
Abstract: DS‐ALL has a higher rate of relapse and treatment‐related mortality. The newer immunotherapies are potentially better options. Relapsed ALL with positive MRD has a poor prognosis. Transient long‐term remission after ALL relapse due to partial chemotherapy combined severe infection is rare. Abstract : DS‐ALL has a higher rate of relapse and treatment‐related mortality. The newer immunotherapies are potentially better options. Relapsed ALL with positive MRD has a poor prognosis. Transient long‐term remission after ALL relapse due to partial chemotherapy combined severe infection is rare.